“Being able to speak English is one thing, knowing how to write it is another” : young Icelanders’ perceptions of writing in English - Anna Jeeves 1954- (2012)
A qualitative study on perceived relevance of secondary school English studies in Iceland is reported. Interviews with secondary school and university students and young people in employment give insight into perceptions of studying English at secondary school. The paper focuses on what value writing in English at school has for students and what changes to classroom material and activities could benefit them. The article opens with a brief overview of recent scholarly discussion on writing in the teaching of English as a foreign language. The 2011 Icelandic national curriculum for secondary schools and the European Language Portfolio are discussed. The findings of the study suggest a need for advanced language accuracy and fluency in employment. Participants enjoy writing in English, but mention a lack of autonomy and self-assessment skills. The article concludes with a discussion of the implications of the study for learners and teachers of English. Greint er frá eigindlegri rannsókn á meintu gildi enskunáms í framhaldsskólum á Íslandi. Viðtöl við framhaldsskóla- og háskólanema, og ungt fólk í atvinnulífinu veita innsýn í viðhorf þeirra til enskunáms í framhaldsskóla. Í greininni er lögð áhersla á hvert viðhorf nemenda er til ritunar á ensku í námi og hvaða breytingar á námsefni og kennsluaðferðum gætu komið þar að gagni. Greinin hefst á stuttu yfirliti um það nýjasta í fræðilegri umfjöllun um ritun í kennslu ensku sem erlends tungumáls. Fjallað er um aðalnámskrá fyrir framhaldsskóla fyrir árið 2011 og Evrópsku tungumálamöppuna. Niðurstöður rannsóknarinnar benda til þess að þörf sé á umtalsverðri nákvæmni og flæði í tungamálakunnáttu þegar kemur út í atvinnulífið. Þátttakendur hafa flestir gaman af því að skrifa á ensku en nefna skort á sjálfstæði og færni í sjálfsmati. Greininni lýkur með umfjöllun um þýðingu rannsóknarinnar fyrir enskunemendur og enskukennara.